Geographic variations in dental sealant utilization by Medicaid enrollees. (11th November 2020) - Okunseri, Christopher E.; Okunseri, Elaye; Garcia, Raul I.; Visotcky, Alexis; Szabo, Aniko
Abstract: Objective: To investigate geographical variations and their relationship to race/ethnicity in dental sealant utilization for first molars among Wisconsin Medicaid enrollees from 2010 to 2013. Methods: Wisconsin Medicaid dental claims for sealants in children aged 6‐16 years were analyzed. County‐level population density, urban influence code, presence of dental health professional shortage areas, and population‐per‐dentist ratio were considered as geographic predictors. Descriptive statistics and mixed effects Poisson regression models were used to examine the effect of county level covariates on the number of dental sealants received per person‐year (PY) of eligibility adjusting for patient‐level characteristics. Over‐dispersion was modeled by a random residual effect, and all models adjusted for single‐year age and gender interaction and race/ethnicity main effect. Results: Medicaid claims for sealants on first permanent molars for 2010–2013 totaled 288, 019 over 1, 130, 000 PY. The age‐ and gender‐standardized rate of first molar sealant applications per 100 PY were 27.9, 25.7, and 16.6 for White, Hispanic, and Black children, respectively. County‐specific rates ranged from a low of 8.9 per 100 PY to a high of 62.6 per 100 PY. In the multivariate analysis after adjusting for geography, compared to Whites, Hispanics had highest rates (rate ratio (RR) = 1.33, 95% CI = 1.30‐1.37) of dental sealant utilization followed by Blacks (RR = 1.25, 95% CI = 1.21‐1.29). Population density was the only significant geographic predictor (RR = 0.56 per 10‐fold increase, 95% CI = 0.45‐0.69). Conclusions: Substantial geographic variability in the utilization of sealants for first molars was identified. Lower population density was the main geographical predictor of high sealant utilization.